Knee valgus during drop jumps in National Collegiate Athletic Association division I female athletes: The effect of a medial post - Joseph, M.; Tiberio, D.; Baird, J. L.; Trojian, T. H.; Anderson, J. M.; Kraemer, W. J.; Maresh, C. M. (The American Journal of Sports Medicine, 2008)
Background: Female athletes land from a jump with greater knee valgus and ankle pronation/eversion. Excessive valgus and pronation have been linked to risk of anterior cruciate ligament injury. A medially posted orthosis decreases component motions of knee valgus such as foot pronation/eversion and tibial internal rotation.